2018
DOI: 10.1111/acel.12767
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CYB5R3 and NQO1, two NAD+‐producing enzymes, mimics aspects of caloric restriction

Abstract: SummaryCalorie restriction (CR) is one of the most robust means to improve health and survival in model organisms. CR imposes a metabolic program that leads to increased stress resistance and delayed onset of chronic diseases, including cancer. In rodents, CR induces the upregulation of two NADH‐dehydrogenases, namely NAD(P)H:quinone oxidoreductase 1 (Nqo1) and cytochrome b 5 reductase 3 (Cyb5r3), which provide electrons for energy metabolism. It has been proposed that this upregulation may be responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 54 publications
2
34
0
Order By: Relevance
“…The internal circadian clock also increases hunger independent of food intake and other behaviors. Intermittent energy restriction increases concentrations of the plasma membrane redox system enzymes, NADHcytochrome b5 reductase and NAD(P)H-quinone oxidoreductase, contributing to oscillations in the NAD(P)H [reduced form of NAD(P) + ] to NAD(P) + (nicotinamide adenine dinucleotide phosphate) ratio (82). The circadian rhythmicity of CLOCK and BMAL1 expression regulates the transcription of NAMPT, a key regulatory enzyme involved in the generation of NAD + , a metabolite required for the deacetylase activity of SIRT1.…”
Section: Intermittent and Periodic Fastingmentioning
confidence: 99%
“…The internal circadian clock also increases hunger independent of food intake and other behaviors. Intermittent energy restriction increases concentrations of the plasma membrane redox system enzymes, NADHcytochrome b5 reductase and NAD(P)H-quinone oxidoreductase, contributing to oscillations in the NAD(P)H [reduced form of NAD(P) + ] to NAD(P) + (nicotinamide adenine dinucleotide phosphate) ratio (82). The circadian rhythmicity of CLOCK and BMAL1 expression regulates the transcription of NAMPT, a key regulatory enzyme involved in the generation of NAD + , a metabolite required for the deacetylase activity of SIRT1.…”
Section: Intermittent and Periodic Fastingmentioning
confidence: 99%
“…We are in the process of completing such an analysis (data not show), which will enable to associate SIRT2 targets with molecular pathways related to CR and provide mechanistic insights. Very recently, Diaz-Ruiz et al showed that upregulation of NQO1, an essential NADH-dehydrogenase that mediates redox control of metabolic homeostasis, mimicks aspects of CR including protection against carcinogenesis in mice (36). Of note, our latest study showed that NQO1 interacts with and activates SIRT2 in an NAD-dependent manner (37).…”
Section: Discussionmentioning
confidence: 80%
“…Noteworthy, although more rarely described, the presence of NQO1 in other subcellular locations such as cytoskeleton may explain other roles of the multifunctional NQO1 protein. For instance, recent studies have supported that NQO1 may provide an adequate supply of NAD + for deacetylase activity of different sirtuins associated with microtubule dynamics [118,124,128]. These studies also highlight the potential plasticity of NQO1 subcellular location during different cellular conditions or stages (e.g.…”
Section: Nqo1 Macromolecular Interactionsmentioning
confidence: 89%
“…In addition, a number of metabolic enzymes in the cytosol and mitochondria (ODC, NDUSF7, NME1, ADK, GOT1, AK4) could also interact with NQO1 in these compartments. Indeed, NQO1 overexpression in mice is known to enhance glycolytic and mitochondrial respiration activities and enhance metabolic flexibility, mimicking the beneficial effects of caloric restriction [124]. It is worth noting that the proteasomal protein degradation machinery may operate through rather similar mechanisms in the cytosol and the nucleus [125,126], and thus, the well-known chaperone role of NQO1 for different protein partners (see Table A2), may indeed operate in the cytosol thus increasing the levels of cytosolic proteins amenable to import to other organelles (such as nucleus or mitochondria; [74,127]) and plausibly by stabilizing these proteins upon import of both the partner and NQO1 in these organelles.…”
Section: Nqo1 Macromolecular Interactionsmentioning
confidence: 99%